2020
DOI: 10.1111/nyas.14458
|View full text |Cite
|
Sign up to set email alerts
|

New insights on brain‐derived neurotrophic factor epigenetics: from depression to memory extinction

Abstract: Advances in characterizing molecular profiles provide valuable insights and opportunities for deciphering the neuropathology of depression. Although abnormal brain‐derived neurotrophic factor (BDNF) expression in depression has gained much support from preclinical and clinical research, how it mediates behavioral alterations in the depressed state remains largely obscure. Environmental factors contribute significantly to the onset of depression and produce robust epigenetic changes. Epigenetic regulation of BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 191 publications
0
21
0
Order By: Relevance
“…Given the previously reported involvement of the hippocampus in the pathophysiology of depression [ 53 ], we selected the dorsal hippocampus to evaluate the expression of plasticity-related genes to identify the molecular effects of HE on depression. We found significant group effects on the gene expression of Bdnf (F (2,12) = 10.213, p = 0.003), Trkb (F (2,12) = 9.143, p = 0.004), Dcx (F (2,11) = 6.810, p = 0.012), Syp (F (2,12) = 12.227, p = 0.001), Nes (F (2,11) = 13.728, p = 0.001), and Psd-95 (F (2,12) = 8.236, p = 0.007) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the previously reported involvement of the hippocampus in the pathophysiology of depression [ 53 ], we selected the dorsal hippocampus to evaluate the expression of plasticity-related genes to identify the molecular effects of HE on depression. We found significant group effects on the gene expression of Bdnf (F (2,12) = 10.213, p = 0.003), Trkb (F (2,12) = 9.143, p = 0.004), Dcx (F (2,11) = 6.810, p = 0.012), Syp (F (2,12) = 12.227, p = 0.001), Nes (F (2,11) = 13.728, p = 0.001), and Psd-95 (F (2,12) = 8.236, p = 0.007) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 A). To elucidate the molecular pathways in the neuroplasticity-related mechanisms, we first assessed the components of BDNF signalling and their involvement in the pathophysiology of depression [ 53 ]. One-way ANOVA revealed a marginally significant difference in the protein expression of TrkB (F (2, 13) = 3.734, p = 0.052) and significant difference in pTrkB level (F (2, 11) = 4.811, p = 0.032).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that both glutamate and GABA levels were lowered in the ventral hippocampus, which might follow the ‘disruption hypothesis’, whereby information flow is disrupted (Chiken & Nambu, 2016). It may be interesting for future studies to examine the cellular modifications, including DNA methylation and histone modifications, considering the large‐scale neurotransmitter changes observed in this study, as such modifications are crucial to the development of anxiety disorders (Hutchinson et al, 2012; Kwapis & Wood, 2014; Poon, Chan, et al, 2020; Poon, Heng, & Lim, 2020). Overall, the findings suggest that the modulation of dopamine transmission plays a major role in the effects of prelimbic cortex DBS, which may also involve multiple neurotransmitters, although future studies are needed to further explore their contributions (Tan, Neoh, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent work has implicated the efficacy of neuromodulation techniques in manipulating fear memory, few studies have systematically studied its effects on individual stages of the memory process and most studies have focused on enhancing memory extinction (Do‐Monte et al, 2013; Milad & Quirk, 2002; Milad et al, 2004; Poon, Heng, et al, 2020; Rodriguez‐Romaguera et al, 2012). Here, we employed a systematic approach to examine the temporal specificity of prelimbic cortex DBS administration and isolate the effects of DBS on the consolidation of memory by stimulating post acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The central mediator of neuronal plasticity, brain-derived neurotrophic factor (BDNF), has been extensively studied for its role in synaptic formation and maintenance, and for the ability of the central nervous system (CNS) to regenerate and adapt to possible damage [ 16 , 17 ]. Higher BDNF levels are associated with better cognitive and psychiatric states in both healthy subjects and depressed patients [ 18 , 19 , 20 ]. However, recent studies have noted significant reductions in BDNF levels in depressed patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%